Aortoenteric Fistula as a Complication of Open Reconstruction and Endovascular Repair of Abdominal Aorta. (14th September 2014) - Tagowski, Marek; Vieweg, Hendryk; Wissgott, Christian; Andresen, Reimer
Abstract : The paper intends to present a review of imaging characteristics of secondary aortoenteric fistula (AEF). Mechanical injury, infection, and adherence of a bowel segment to the aorta or aortic graft are major etiologic factors of AEF after open aortic repair. The pathogenesis of AEF formation after endovascular abdominal aortic repair is related to mechanical failure of the stent-graft, to stent graft infection, and to persistent pressurization of the aneurysmal sac. The major clinical manifestations of AEF comprise haematemesis, melaena, abdominal pain, sepsis, and fever. CT is the initial diagnostic modality of choice in a stable patient. However, the majority of reported CT appearances are not specific. In case of equivocal CT scans and clinical suspicion of AEF, scintigraphy, 67 Ga citrate scans or 18 F-FDG PET/CT is useful. Diagnostic accuracy of endoscopy in evaluation of AEF is low; nevertheless it allows to evaluate other than AEF etiologies of gastrointestinal bleeding. Without adequate therapy, AEF is lethal. Conventional surgical treatment is associated with high morbidity and mortality. The endovascular repair may be an option in hemodynamically unstable and high-risk surgical patients. We also illustrate an example of a secondary AEF with highly specific albeit rare radiologic picture from our institution.